INOVASI PRODUK PERCETAKAN PADA PERUSAHAAN FIRGIE PRINTING DI DESA CANGGU KECAMATAN KUTA UTARA KABUPATEN BADUNG - Junaidi Abdillah; Sutrisno Djaja (Economic Education, University of Jember, 2016)
This research was conducted to find out the kind and innovation of printing product at Firgie Printing Company. This research kind is descriptive qualitative. The determination of the location of research using the method of purposive area in Firgie Printing Company at Jalan Pura Wates number 34 Canggu Village, District North Kuta, Badung. The determinan of the informants of techniq using purposive sampling. The subject of this research is all part of organization Firgie Printing Company and the consumer printing product Firgie Printing Company. Data collection technique used consisted of interview method, of observation, and documentation. Data analysis technique used is data reduction, data display, and conclusion drawing/verification. The result showed Firgie Printing Company produce six kind of printing product, it is hang tag, paper bag, box printing, label printing, name card, and brosur. The innovative printing product from Firgie Printing Company is hang tag Aloha Lani Law, hang tag Muchacho and name card Sarti Restaurant, because it’s fulfill the principle of innovative product.